Is the Faculty of Family Planning and Reproductive Health Care Guidance on emergency contraception being followed in general practice? An audit in the West Midlands, UK. Issue 3 (1st July 2007) - Bannister, Lisa; Macve, Joanna; Pinkey, Benjamin; Webberley, Helen
Abstract : Background and methodology: In 2003, the Faculty of Family Planning and Reproductive Health Care (FFPRHC) of the Royal College of Obstetricians and Gynaecologists published guidance on emergency contraception (EC). A literature search revealed no published work describing doctors' actions when prescribing EC. In order to assess the extent to which the FFPRHC Guidance is being followed in general practice, an audit of the medical notes of women requesting EC between January 2003 and December 2004 in six general practice surgeries located in the West Midlands, UK was conducted. From the medical notes, discussions between health care professionals and patients requesting EC regarding ongoing contraceptive needs, the risk of sexually transmitted infections (STIs) and the availability of the emergency intrauterine device (IUD) were recorded. Results: A total of 718 emergency contraceptive pill consultations were analysed. The median age for presentation was 24 years. The 20–24 years age group accounted for the most consultations (30.9%). In 40% of consultations there was no evidence of future contraceptive needs having been discussed. Only 20 (2.8%) consultation notes contained evidence that STIs had been discussed. Chlamydia tests were undertaken in only 15/718 (1.7%) consultations. In only 10 (1.4%) of the consultations was the IUD discussed with the patient as an alternative form of EC. Discussion and conclusions: This audit suggests that the FFPRHC Guidance on EC is not being followed in general practice, and therefore patients requesting EC may not be receiving the highest standard of care.